Oscillatory Control of Factors Determining Multipotency and Fate in Mouse Neural Progenitors - Imayoshi, Itaru; Isomura, Akihiro; Harima, Yukiko; Kawaguchi, Kyogo; Kori, Hiroshi; Miyachi, Hitoshi; Fujiwara, Takahiro; Ishidate, Fumiyoshi; Kageyama, Ryoichiro (Science (American Association for the Advancement of Science), 2013)
The basic helix-loop-helix transcription factors Ascl1/Mash1, Hes1, and Olig2 regulate fate choice of neurons, astrocytes, and oligodendrocytes, respectively. These same factors are coexpressed by neural progenitor cells. Here, we found by time-lapse imaging that these factors are expressed in an oscillatory manner by mouse neural progenitor cells. In each differentiation lineage, one of the factors becomes dominant. We used optogenetics to control expression of Ascl1 and found that, although sustained Ascl1 expression promotes neuronal fate determination, oscillatory Ascl1 expression maintains proliferating neural progenitor cells. Thus, the multipotent state correlates with oscillatory expression of several fate-determination factors, whereas the differentiated state correlates with sustained expression of a single factor.